2016
DOI: 10.1038/scsandc.2016.16
|View full text |Cite
|
Sign up to set email alerts
|

Long-term paired associative stimulation can restore voluntary control over paralyzed muscles in incomplete chronic spinal cord injury patients

Abstract: Emerging therapeutic strategies for spinal cord injury aim at sparing or restoring at least part of the corticospinal tract at the acute stage. Hence, approaches that strengthen the weak connections that are spared or restored are crucial. Transient plastic changes in the human corticospinal tract can be induced through paired associative stimulation, a noninvasive technique in which transcranial magnetic brain stimulation is synchronized with electrical peripheral nerve stimulation. A single paired associativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
78
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(91 citation statements)
references
References 32 publications
10
78
0
Order By: Relevance
“…Our aim was to develop and test tools for patient rehabilitation, and the observed increase of efficacy of the motor activation by the PAS is promising in this respect. The results support the usefulness of the stimulation parameters selected for our proof of concept—study of PAS used in rehabilitation of two patients with spinal cord injuries (Shulga et al, 2016 ).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Our aim was to develop and test tools for patient rehabilitation, and the observed increase of efficacy of the motor activation by the PAS is promising in this respect. The results support the usefulness of the stimulation parameters selected for our proof of concept—study of PAS used in rehabilitation of two patients with spinal cord injuries (Shulga et al, 2016 ).…”
Section: Discussionsupporting
confidence: 74%
“…For PNS, we used high-frequency peripheral pulses at minimal intensity required to elicit F-response to ensure the activation of the motor neurons. We have previously reported the use of otherwise identical protocol in one healthy subject at intensity higher than minimal intensity for F-response (15 mA); this has led to MEP potentiation observable at 1 h, but not immediately after PAS (Shulga et al, 2016 ). Lowering the intensity in the same subject to 11 mA (subject 1 in this study) has led to observable MEP potentiation immediately after the protocol.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…9 Applied together, PNS and TMS are called paired associative stimulation (PAS) and are believed to strengthen excitatory synapses and inducing neural plasticity. 10 Depending on intervals between these two stimuli, PAS may induce long term inhibition or potentiation (LTP) underlaying neuro plasticity that correlates with an increase in muscle voluntary force. 11 Previous research suggested that spike timing-dependent plasticity of residual corticospinal-motoneuronal synapses after SCI could be a promising therapeutic target.…”
Section: Introductionmentioning
confidence: 99%